Compressed Natural Gas Vehicles: Financially Viable Option?. Issue 1 (2016) - Soltani-Sobh, Ali; Heaslip, Kevin; Bosworth, Ryan; Barnes, Ryan
Natural gas vehicles are being developed because of increasing concerns about energy dependence, air quality and emissions, and, more recently, climate change. The major advantage of natural gas vehicles is their lower fuel cost. Several economic and technical factors such as limited range and availability of relevant infrastructure prevent widespread adoption of natural gas vehicles. A model for the financial analysis of the possibility of compressed natural gas (CNG) vehicles being competitive with gasoline-powered vehicles is offered. The model evaluates the extent to which commuters find adoption of CNG vehicles to be economically viable in the United States. The results indicate that the percentage of commuters who would adopt CNG vehicles is small, even if fueling infrastructure were fully developed and CNG vehicles were widely available for purchase. A larger number of vehicle miles traveled and increased gasoline prices encourage commuters to adopt CNG vehicles, while higher fuel economy and purchase price differentials result in lower adoption rates. In some cases, which vary in accordance with the values of the model's parameters, commuters purchase a CNG vehicle as their second car and keep a gasoline-powered car as their first.